A teachers' orientation approach to understand the university teacher-student relationship - Inés Küster-Boluda; Natalia Vila-López (Universidad de Navarra, 2021)
This research intends to advance the understanding of the university teacher-student relationship in the context of teachers' market orientation with the aim to improve students' performance. Thus, the study is articulated on three axes: the students' performance approach, the relationship among diverse aspects of teachers, and, fi nally, the effect of these aspects on students' performance. The results gained from a sample of 45 teachers and 932 students show that teachers' student orientation infl uences perceived learning and student satisfaction. Other interesting results are also attained that lead to certain conclusions and implications.